Lessons from the great recession at the crossroads of sustainability and recovery - Gurdgiev, Constantin T.; Leonard, Liam; Gonzalez-Perez, Maria-Alejandra (Advances in sustainability and environmental justice ;, 2016)
This volume examines global cases of environmental sustainability and economics in the context of nations from multi-disciplinary perspectives. This book analyses the problems faced globally as economies try to build a sustainable future in the aftermath of the 'Great Recession', and the recent economic and financial crises.